Unusual fluorescence behaviour of a heteroleptic Cu(i) complex featuring strong electron donating groups on a diimine ligand. (4th January 2022) - Santander-Nelli, Mireya; Sanhueza, Luis; Navas, Daniel; Rossin, Elena; Natali, Mirco; Dreyse, Paulina
Abstract : Synthesis of a novel bulky diimine ligand and its corresponding heteroleptic Cu(i ). Unusual fluorescence behavior of a novel Cu(i ) complex due to a strong electron-donor diimine ligand. Abstract : A novel diimine ligand (N^Nb ) and the corresponding heteroleptic diimine–diphosphine Cu(i ) complex (Cu–N^Nb ) have been synthesized and their structural properties characterized. The N^Nb ligand is [2, 9-bis-[4-(dimethylamino)phenyl]ethenyl]-4, 7-diphenyl-1, 10-phenanthroline, which has a bulky structure designed to retain the tetrahedral geometry of the corresponding Cu(i ) complex in the excited state in order to avoid potential quenching by flattening distortion. The corresponding Cu(i ) complex comprises the mentioned diimine ligand and bis-[2-(diphenylphosphino)-phenyl]ether (POP) as the diphosphine ligand. The electrochemical and photophysical properties, suitably complemented by theoretical calculations, have been studied and compared to those of a reported heteroleptic Cu(i ) complex including POP and bathocuproine as the diphosphine and diimine ligands, respectively. According to both experimental and computational data, the new complex Cu–N^Nb is characterized by an unexpected luminescence behaviour that markedly differs from those typically encountered in heteroleptic diimine–diphosphine Cu(i ) complexes and stems from the direct, spin-allowed radiative decay (fluorescence) of an intraligand charge transfer excited state on the bulky diimine ligand. The emission quantum yield is also surprisingly high (35%), possibly inspiring potential and alternative applications of this novel complex in luminescent devices or imaging.